Impaired generation of new subcategories and switching in a semantic verbal fluency test in older adults with mild cognitive impairment - Bertola, Laiss; Cunha Lima, Maria Luiza; Romano-Silva, Marco A.; de Moraes, Edgar N.; Diniz, Breno Satler; Malloy-Diniz, Leandro F. (Frontiers in Aging Neuroscience, 2014)
The semantic verbal fluency task is broadly used in the neuropsychological assessment of elderly subjects. Even some studies have identified differences in verbal fluency clustering and switching measures between subjects with normal aging and a clinical condition such as Mild Cognitive Impairment (MCI) and Alzheimer’s disease, the results are not always consistent. This study aimed to compare clustering and switching measures of an animal’s semantic verbal fluency task among normal controls (n=25), amnestic Mild Cognitive Impairment (aMCI; n=25), amnestic multiple domain Mild Cognitive Impairment (a+mdMCI; n=25) and Alzheimer’s disease (AD; n=25) Brazilian subjects. The analyses were executed considering three (unifying the MCI subtypes) and four groups. As the data were not normally distributed, we carried out non-parametric tests (Kruskal-Wallis and Mann-Whitney tests) to evaluate the differences in performance in the measures of the verbal fluency test among the groups. The comparison demonstrated that the groups differed in the total of correct words produced, number of clusters and switching but the measure of new subcategories was the only with significant difference among the NC and all the clinical groups. The measure of new subcategories is the number of original subcategories inside the higher category of animals that the subject produced, such as farm, domestic, African animals. Our results indicate that semantic memory impairment is a visible and recent deficit that occurs even in non-demented subjects with very mild cognitive impairment and the implications of theses findings are discussed.